2022
DOI: 10.3390/su141610267
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Transportation Industry Efficiency, Transportation Structure, and Regional Sustainability Development in China: Based on DEA and PVAR Models

Abstract: The sustainable development of the transportation industry has always been a major concern after China’s reform and opening up. Existing studies only examine the transportation efficiency of a single mode of transportation or a certain region without considering the overall efficiency of the national transportation industry. Furthermore, most studies do not consider the impact of transportation structure on transportation efficiency and economic development. Moreover, the correlations and interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Khanh Van et al (2022) studied the spatial efficiency of the transportation system using the Charnes-Cooper-Rhodes model and showed that the remaining capacity of parking lots in Sapporo City reached 27.81%, and the density of bus stops and roads exceeded demand by about 14%. Li et al (2022) used a three-stage DEA model to assess the efficiency of the transportation industry and used a panel vector autoregressive model to analyze the interaction between traffic structure, transportation efficiency, and regional economic development. Karlaftis (2004) used DEA to demonstrate that the efficiency and effectiveness of a transportation system are positively correlated and that the optimal size of a transportation system varies with the evaluation metric.…”
Section: Non-parametric Methodsmentioning
confidence: 99%
“…Khanh Van et al (2022) studied the spatial efficiency of the transportation system using the Charnes-Cooper-Rhodes model and showed that the remaining capacity of parking lots in Sapporo City reached 27.81%, and the density of bus stops and roads exceeded demand by about 14%. Li et al (2022) used a three-stage DEA model to assess the efficiency of the transportation industry and used a panel vector autoregressive model to analyze the interaction between traffic structure, transportation efficiency, and regional economic development. Karlaftis (2004) used DEA to demonstrate that the efficiency and effectiveness of a transportation system are positively correlated and that the optimal size of a transportation system varies with the evaluation metric.…”
Section: Non-parametric Methodsmentioning
confidence: 99%
“…Regarding measurement methodologies, scholars have quantified factor misallocation by determining the extent of factor distortion in resource allocation using a profit function [21][22][23] , based on the efficiency loss measurement framework constructed by Hsieh and Klenow in 2009 24 . However, more scholars focus on the relative efficiency loss to reflect transportation resource misallocation 19,25 , such as Bai et al (2021) and Tiwari et al (2023) employed data envelopment analysis to evaluate the efficiency of state-owned transportation sectors in China's railroads and India's roads 26,27 ; Li et al ( 2022) assessed the overall efficiency of China's transportation industry using PVAR Models 19 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the selection of indicators, scholars not only consider common ones like capital 15 and labor 16 , but also incorporate additional indicators into the evaluation of transportation resources misallocation, such as differences in the size of regional road networks with expressway attributes 17 , transportation demand 18 , transportation structure 19 , travel choice and travel cost 20 , and other indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on regional sustainable development mainly explores areas such as land resources and environmental protection [ 28 , 29 ], industrial and economic development [ 30 , 31 ], government institutional mechanisms [ 32 ], and transportation and infrastructure [ 33 , 34 ]. Recently, some scholars have paid attention to the spatial distribution differences of cities’ sustainable development degree in the region and the driving effects of regional sustainable development [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%